Effect of Aerobic and Resistant Exercise Intervention on Inflammaging of Type 2 Diabetes Mellitus in Middle-Aged and Older Adults: A Systematic Review and Meta-Analysis - Xing, Huimin (ELSEVIER SCIENCE INC, 2023)
10.1016/j.jamda.2022.01.055